2013
DOI: 10.1002/pip.2398
|View full text |Cite
|
Sign up to set email alerts
|

High‐efficiency microcrystalline silicon single‐junction solar cells

Abstract: This short communication highlights our latest results towards high-efficiency microcrystalline silicon single-junction solar cells. By combining adequate cell design with high-quality material, a new world record efficiency was achieved for single-junction microcrystalline silicon solar cell, with a conversion efficiency of 10.69%, independently confirmed at ISE CalLab PV Cells. Such significant conversion efficiency could be achieved with only 1.8 mm of Si.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 39 publications
(45 reference statements)
0
82
2
Order By: Relevance
“…The optical losses are most sensitive to metal textures with dimensions ranging from 30 to 100 nm [33,35]. The optical losses can be reduced, but not prevented by inserting a dielectric layer with a low refractive index between the metal back reflector and the silicon solar cell [3,4,6,27,35]. In the current study, and in most studies in the literature, a sputtered metal oxide film, e.g., zinc oxide, is inserted between the metal back reflector and the silicon solar cell.…”
Section: Comparison Of Contact and Absorber Textured Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical losses are most sensitive to metal textures with dimensions ranging from 30 to 100 nm [33,35]. The optical losses can be reduced, but not prevented by inserting a dielectric layer with a low refractive index between the metal back reflector and the silicon solar cell [3,4,6,27,35]. In the current study, and in most studies in the literature, a sputtered metal oxide film, e.g., zinc oxide, is inserted between the metal back reflector and the silicon solar cell.…”
Section: Comparison Of Contact and Absorber Textured Solar Cellsmentioning
confidence: 99%
“…Experimentally, high conversion efficiencies have been achieved by texturing the contact layers of silicon solar cells [2][3][4][5][6][7][8][9]. The nanotextured contact layers reduce reflection losses and enhance the scattering and diffraction of light within the solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…IV curve of a micromorph cell with an efficiency of 11.75%, deposited using highly transparent ZnO electrodes. and the SiO-based IRL were made in an Octopus I cluster tool made by INDEOtec SA, whereas the µc-Si:H cell was made in a research-scale reactor developed in-house [27]. Figure 5 shows various spectra obtained when simulating this set of experimental data with the model presented in reference [7].…”
Section: Resultsmentioning
confidence: 99%
“…We investigate processes which target high material growth rates to reduce the fabrication costs per unit and to increase the throughput of the deposition system. Studies on how to reach world record solar cell efficiencies were given by Hänni et al [6] for μc-Si:H single junction solar cells and by Kim et al [7] and Guha et al [8] for multijunction solar cells. Further details about the recent developments in the field of thin-film solar cells from research a e-mail: ma.meier@fz-juelich.de scale to industrial scale can be found in a comprehensive overview published by Shah et al [9].…”
Section: Introductionmentioning
confidence: 99%